Banking and Finance Management System Human Resource IV: (HR Analytics, Core Human Capital, Compensation Planning, and Administrative Payroll): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
When we think of a bank, we often associate it with handling money. While this is technically correct, Brianna Whiting explains that a banking system is a collection of institutions that offer financial services to the public. These services include payment systems, loans, deposits and investment assistance. While banks have many functions, their main role is to collect funds from those with money, pool them together and lend them to those who need them. Human Resource 4 is a software designed to help businesses manage employee data more efficiently. It combines various systems and processes, allowing companies to easily store employee data, manage payroll, oversee recruitment processes, administer benefits, and track attendance records. The software comprises five sub-modules: Core Human Capital, HR Analytics, Compensation Planning, and Payroll.The project team utilised the Agile Scrum methodology to develop the system. This methodology is ideal for businesses that require quick project completion. Agile means "incremental", allowing the team to develop projects in small increments. Scrum is an Agile methodology that divides projects into "sprints" for better management. The project team analysed the existing system to determine problems and gathered the necessary information to create a new solution. They ensured that the design and development of the system met all requirements. Core Human Capital Management is the primary focus of every employee in an organisation. It is a tool for recruiting, managing and developing employees to reach their full potential. It provides a list of employee information. HR Analytics offers dashboards for the user to view the percentage of each employee. Compensation Planning provides payment for each employee based on their worked hours, and it deals with legal documents such as SSS, PHILHEALTH and PAGIBIG. Payroll calculates payment for each employee and generates payslips. The proposed system is highly computerised, ensuring that user account data is secure and accurate, reducing the risk of human error or machine damage. This efficient system offers quick access to banking services, saving customers time compared to traditional banking systems. The data entry screen is user-friendly and allows for easy data manipulation. This system is designed to be easy to use and improve the quality of processes and transactions, and only authorised users can access it.